Searching for the Virtues of the European Model - Saint-Paul, Gilles (IMF Working Papers; Working Paper, 1994)
The distributional effects of the minimum wage are analyzed in a model where skilled and unskilled labor enter the production function. It is argued that distributional goals are best achieved by letting the labor market clear and achieving redistribution through taxes and transfers.